'Nissabacter archeti' gen. nov., sp. nov., a new member of Enterobacteriaceae family, isolated from human sample at Archet 2 Hospital, Nice, France. (May 2017) - Mlaga, K.D.; Lotte, R.; Montaudié, H.; Rolain, J.-M.; Ruimy, R.
Abstract: We propose the main characteristics of a new bacterium species named Nissabacter archeti strain 2134 (CSURP3445 = LT631518), isolated from pustule scalp of a 29-year-old man at hospital Archet 2, Nice, south of France.